Sistem Pendukung Keputusan Metode SMART Dalam Penentuan Pemberian Bantuan Sosial Berdasarkan DTKS Di Desa Bebengan - Nurhidayat, Ahmad; supriyanto, Aji; Nurraharjo, Eddy (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The level of welfare of the people in Indonesia is still low which results in the number of poverty is high. In an effort to reduce poverty in Indonesia, the government provide social assistance to provide capital or meet needs community food. There is a lot of help to make the shortage of help not right on target. In this effort, this research builds a support system decision by referring to the Integrated Community Welfare Data (DTKS) as the criteria. The DTKS data only contains BPS data for 2019 and not yet there periodically. Therefore, DTKS is needed to verify the poor restrictions on covid 19. This system aims to make it easier for Bebengan village officials in deciding the provision of social assistance to the community. methods that can be used The method used in this system is the SMART (Simple Multi Attribute Rating) method Technique). The SMART method is a fast multi-criteria retrieval technique and easy to use. To determine potential recipients of social assistance based on 10 criteria, namely: house conditions, water sources, income, electricity voltage, Education, employment, air resources, cooking fuel, age, dependents. Based on these 10 criteria, a decision support system is drawn up with: using intelligent methods, Decision Support System is a system computers that process data into information and decisions. From the criteria that given that the mother of the wife gets the top ranking as the top alternative with value 93.